Group portrait of Lincoln High School students - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing students in front of the San Jose, California's Lincoln High School building. Against the backdrop of American flags, students can be seen holding up smaller flags on which are written the names of countries from around the world. One adult, visible to the left of a statue of Abraham Lincoln (image center) is holding a sign that reads: " 63 years ago I cast my first ballot, on the battle field, for 'Old Abe' and against human slavery."